Physical fitness assessment tools for children with developmental coordination disorder and their feasibility for low-income settings: A systematic review - Monica Maria do Nascimento; Jorge Lopes Cavalcante-Neto; Meyene Duque Weber; Paula Cristina dos Santos Rodrigues; Andreia N. Pizarro; Maria Olga Fernandes Vasconcelos (Journal of Exercise Science & Fitness)
Background/objectives: This study systematically reviewed the literature on physical fitness assessment tools for children with developmental coordination disorder compared with typically developing children aged 7 to 10 and analyzed the feasibility of these tools for use in low-income settings. Methods: Searches were conducted in the PubMed, Scopus, Web of Science, and EBSCO/RIC databases. The Newcastle - Ottawa Quality Assessment Scale assessed the methodological quality of the studies, and a checklist adapted from COSMIN assessed the feasibility of the instruments. Results: From 8470 studies initially retrieved, 21 were included in this systematic review. The most assessed physical fitness components in children with developmental coordination disorder compared with typically developing children were cardiorespiratory fitness and muscle strength. Most studies had high methodological quality. The shuttle run (cardiorespiratory fitness) and handgrip dynamometer (muscle strength) were the most used tools. The PERF-FIT, long jump, and 6-min walk test were considered the most feasible tools for low-income settings, while the incremental treadmill test was deemed the least feasible. Conclusion: The findings evidenced several viable tools for testing physical fitness in children with DCD compared to typically developing peers from low-income countries. The most viable, as PERF-FIT, long jump and 6-min walk test should be used on large scale in low-income settings.